High‐resolution mass spectrometry (HRMS): Focus on the m/z values estimated by the Savitzky–Golay first derivative. (15th January 2021) - Boulet, Jean‐Claude; Meudec, Emmanuelle; Vallverdu‐Queralt, Anna; Cheynier, Véronique
Abstract : Rationale: The calculation of centroids from profile mass spectra is one of the very first steps in the processing of mass spectra. The output is a signal and a m/z value. We focus on the accuracy of the prediction of the centroids' m/z values. Methods: A calculation based on the Savizky–Golay algorithm was evaluated on an Orbitrap mass spectrum. Reference m/z values were identified manually. Experimental centroids were extracted (1) automatically using our algorithm or the MSconvert algorithm and (2) manually using the Xcalibur software from Thermo. The three series of experimental m/z values were compared with the reference m/z values. Results: Our algorithm improved the determination of the m/z values compared with MSconvert. However, no improvement was observed over Xcalibur. Conclusions: Our algorithm improved the automatic estimation of m/z values in the profile‐to‐centroid calculation. This is of importance when the goal is to determine raw compositions from the experimental m/z values. Nevertheless, the algorithms led to almost the same m/z values on a higher resolution mass spectrum.